Business education, innovation skills as predictors of entrepreneurial self-efficacy in university students - Laydes, Marbelith; Vásquez, Mery; Cruz-Tarrillo, Joel; Diaz, Robin Alexander (Journal of Business Economics and Management, 2024)
Considering the importance of entrepreneurship education in the social and economic sphere, the objective of this study was to examine how entrepreneurship education influences the development of innovative skills and entrepreneurial confidence of university students. To do this, it was necessary to adopt a quantitative methodological perspective to understand the relationship between the study variables. Through the application of confirmatory factor analysis (CFA) and the development of the structural equation model (SEM), it was possible to know and confirm the effect and statistical relationship between the variables. The participants of this research were made up of a total of 701 students under quota sampling selection. Entrepreneurship education has been found to significantly influence the promotion of innovative skills and the development of entrepreneurial self-efficacy. Furthermore, the study reveals that the acquisition of innovation competencies is a prerequisite for students to perform well in the business environment. These competencies not only enable them to adapt to changing environments but also foster creativity, systems thinking, and effective problem-solving. This study provides empirical evidence that entrepreneurship education is a relevant factor in strengthening and developing students’ innovation competencies and entrepreneurial self-efficacy.